Blood Flow Restriction Therapy: An Evidence-Based Approach to Postoperative Rehabilitation. Issue 10 (3rd October 2022) - Watson, Richard; Sullivan, Breanna; Stone, Austin; Jacobs, Cale; Malone, Terry; Heebner, Nicholas; Noehren, Brian
Abstract : ➢ Blood flow restriction therapy (BFRT) involves the application of a pneumatic tourniquet cuff to the proximal portion of the arm or leg. This restricts arterial blood flow while occluding venous return, which creates a hypoxic environment that induces many physiologic adaptations. ➢ BFRT is especially useful in postoperative rehabilitation because it produces muscular hypertrophy and strength gains without the need for heavy-load exercises that are contraindicated after surgery. ➢ Low-load resistance training with BFRT may be preferable to low-load or high-load training alone because it leads to comparable increases in strength and hypertrophy, without inducing muscular edema or increasing pain.